Memahami Anak Berbakat Istimewa (Talented) Serta Penerapan Model Pembelajarannya - Puspitasari, Yeni; Lestari, Puja (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to explore effective approaches in understanding special gifted children and implementing appropriate learning models. The research was conducted using analysis of the latest literature and relevant research as well as the latest theory, through case studies that have inclusive education programs for special gifted children. The results of this research show that a deep understanding of the characteristics of special gifted children is very important in designing effective learning models. In addition, it was found that differentiation and project-based learning models were effective approaches in accommodating the individual needs of special gifted children. The practical implications of this research highlight the need for better training for teachers to understand and implement learning models that suit the needs of special gifted children.